2014
DOI: 10.1176/appi.ajp.2013.12111467
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Use of Serotonin Reuptake Inhibitors and Risk of Upper Gastrointestinal Bleeding

Abstract: Short-term SSRI use (7-28 days) is significantly associated with upper gastrointestinal bleeding. Gender differences may exist in the relationship between SSRI use and upper gastrointestinal bleeding. Physicians should carefully monitor signs of upper gastrointestinal bleeding even after short-term exposure to SSRIs, as is done with nonsteroidal anti-inflammatory drugs and aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 36 publications
(48 reference statements)
3
62
1
7
Order By: Relevance
“…Approximately half of all patients started on these agents experience GI side effects mainly in the first few days/weeks following treatment initiation [29,30]. Short-term SSRI use (7-28 days) is significantly associated with upper GI bleeding, suggesting that the same precautions that are used with nonsteroidal anti-inflammatory drugs and aspirin are appropriate [31]. Some studies have found nausea and vomiting to be one of the most common reasons for treatment discontinuation [32,33].…”
Section: Gastrointestinalmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of all patients started on these agents experience GI side effects mainly in the first few days/weeks following treatment initiation [29,30]. Short-term SSRI use (7-28 days) is significantly associated with upper GI bleeding, suggesting that the same precautions that are used with nonsteroidal anti-inflammatory drugs and aspirin are appropriate [31]. Some studies have found nausea and vomiting to be one of the most common reasons for treatment discontinuation [32,33].…”
Section: Gastrointestinalmentioning
confidence: 99%
“…The use of SSRIs could be associated with an increased risk of upper GI bleeding [31,127]. The overall risks are substantially higher among individuals on concomitant use of nonsteroidal anti-inflammatory agents [127,128].…”
Section: Bleedingmentioning
confidence: 99%
“…Administration of these antidepressants has been also successfully used as a treatment for gastrointestinal diseases, such as motility disorder and gastrointestinal bleeding [92,119], confirming comorbidity of these disorders, but exert a puzzling effect on the intestinal bacterial composition.…”
Section: Gut Microbiota and Serotonin Productionmentioning
confidence: 99%
“…The accuracy of diagnosis of major diseases in the NHIRD has been validated in several studies. [17][18][19] All information that could potentially identify an individual patient was encrypted. Confidentiality of data was maintained in accordance with the data regulations of the Bureau of National Health Insurance and the National Health Research Institute.…”
Section: Data Sourcesmentioning
confidence: 99%